2006
DOI: 10.1002/app.25333
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of polypropylene/sugarcane Bagasse composites

Abstract: To determine the possibility of using sugarcane bagasse (SCB) waste as reinforcing filler in the thermoplastic polymer matrix, SCB-reinforced polypropylene (PP) composites were prepared. The PP and SCB composites were prepared by the extrusion of PP resin with 5, 10, 15, and 20 wt % of SCB filler in a corotating twin screw extruder. The extruded strands were cut into pellets and injection molded to make test specimens. These specimens were tested for physicomechanical properties such as tensile, flexural, Izod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
3
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 39 publications
3
35
3
2
Order By: Relevance
“…Some studies have shown that notched IZOD impact strength generally decreases with increasing filler content (Stark and Berger 1997;Ayrilmis and Kaymakci 2013). However, other researchers have found that wood fiber polypropylene composites exhibit no reduction in notched IZOD impact strength compared to the neat thermoplastic as the filler content increases (Hristov et al 2004;Ramaraj 2007;Karmarkar 2007). Also, contrary to this study, Myers et al (1991) found that inclusion of MAPE had a negative effect on notched impact strength of pine WPC compared to those specimens without MAPE.…”
Section: Impact Strengthcontrasting
confidence: 75%
See 1 more Smart Citation
“…Some studies have shown that notched IZOD impact strength generally decreases with increasing filler content (Stark and Berger 1997;Ayrilmis and Kaymakci 2013). However, other researchers have found that wood fiber polypropylene composites exhibit no reduction in notched IZOD impact strength compared to the neat thermoplastic as the filler content increases (Hristov et al 2004;Ramaraj 2007;Karmarkar 2007). Also, contrary to this study, Myers et al (1991) found that inclusion of MAPE had a negative effect on notched impact strength of pine WPC compared to those specimens without MAPE.…”
Section: Impact Strengthcontrasting
confidence: 75%
“…However, this trend has been seen in other studies involving biofiber/polypropylene composites (Hristov et al 2004;Ramaraj 2007). The elongation to break is a relatively slow and large deformation process that is sensitive to the initiation of cracks at the incompatible material interface of the wood fiber and HDPE.…”
Section: Impact Strengthmentioning
confidence: 87%
“…Então, uma solução composta por 0,08 mL H 2 SO 4 e 9 mL de ácido acético foi adicionada ao sistema, o qual foi agitado durante exemplo, a utilização da celulose para a produção de álcool pelo processo de hidrólise enzimática e hidrólise ácida [3][4][5] , produção de compósitos [6] e derivados celulósicos [7][8][9][10] . O acetato de celulose (AC), Figura 1, é um dos derivados da celulose com maior importância comercial, principalmente devido às seguintes propriedades: é um polímero neutro, tem a capacidade de formação de filmes transparentes e tem um baixo custo.…”
Section: Acetilação Da Celulose Do Bagaço De Cana-de-açúcarunclassified
“…Fungal decay also resulted in an increase in water absorption of composites with the highest amount corresponding to the 4 months exposure. Ramaraj ( 2007 ) examined the effect of SCB powder on the mechanical and thermal properties of the PP matrix by incorporating SCB powder (passing through a 1.5 mm size screen) in PP as a reinforcing fi ller. PP was compounded with 5, 10, 15 and 20% SCB fi ller in a co-rotating twin-screw extruder and injection which was moulded to create a specimen for testing.…”
Section: Assessing Composite Performancementioning
confidence: 99%